Association Between Quality Management Implementation and Inpatient Satisfaction: A Cross-Sectional Study - Irwan; Mahar Muharram Hamzah Assabrum Malik (PT. Nasyah Medika Care, 2024)
Background: Quality management is an essential component of healthcare delivery that aims to improve service quality, patient safety, and organizational performance. Effective implementation of quality management is expected to enhance patient satisfaction, particularly in inpatient services at primary healthcare facilities. Identifying the relationship between quality management implementation and inpatient satisfaction is important for developing strategies to improve healthcare quality and patient-centered services. Research Objective: This study aimed to determine the relationship between quality management implementation and inpatient satisfaction at Antang Public Health Center, Makassar, Indonesia. Methods: This analytical observational study employed a cross-sectional design. A total of 22 inpatients were recruited using a purposive sampling technique. Data on quality management implementation and inpatient satisfaction were collected using structured questionnaires. Data were analyzed using descriptive statistics and the Chi-square test with a significance level of p < 0.05. Results: Most respondents perceived the implementation of quality management as good (68.2%), while 72.7% reported being satisfied with inpatient services. Bivariate analysis revealed a statistically significant relationship between quality management implementation and inpatient satisfaction (p = 0.003). Respondents who perceived good quality management implementation demonstrated a higher level of satisfaction than those who perceived poor implementation. Conclusion: Quality management implementation was significantly associated with inpatient satisfaction at Antang Public Health Center, Makassar. Strengthening leadership commitment, continuous quality improvement, adherence to standard operating procedures, and patient-centered care is essential to improve healthcare quality and enhance patient satisfaction in primary healthcare settings.